“Caracterización del chorizo ahumado con la adición de lactosuero” - Herrera Castillo, Jonatan David (2023)
The smoked chorizo with the addition of whey was made to give better use to the whey that is discarded from the dairy industries. For the elaboration of this sausage, the following procedure was carried out: reception of the material (fresh and acid whey), grinding, mixing of the raw material allowing each of the ingredients to be unified, thus forming a homogeneous mass (addition of the two types of frozen whey), sausage using natural pig casing, then proceed to smoking, in this step depending on the amount of whey used in each chorizo, its smoking varied in time, vacuum packed, then it was stored at a temperature of 4 - 5 ºC. The experimental design used in this research project is a completely randomized design (DCA) with a factorial arrangement AxB (2x3). The best treatment was obtained through the following analyses: sensory, it was determined through a survey of a group of 12 students from the Technical University of Cotopaxi, the following parameters Color, Smell, Flavor and Texture were considered, resulting in the best treatment is the T1(a1 b1) made with (16.78% fresh whey ice) obtaining the different results in terms of: Color (Red), Smell (Characteristic of smoke), Flavor (Pleasant) and Texture (Solid). After 3 days of storage, the physicochemical analysis was carried out and the following was obtained: Ash (3.8%), Moisture (50.0%) and pH (6.17), in addition a microbiological analysis was carried out obtaining: as a count of Escherichia Coli (